Job Security Research in Global Perspective: A Bibliometric Mapping - Hidayat, Rahmat; Bahri, Syamsul; Pulungan, Nurhamidah (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to conduct a comprehensive bibliometric mapping of the development of the global literature on job security in the period 2020 to 2025, including publication trend analysis and keyword mapping of themes, as well as network visualization. This research is bibliometric research, where bibliometric research is a systematic study conducted on the scientific literature to identify, explore, analyze patterns, trends, and impacts in certain fields. Search the article database on the Google Scholar page using Publish or Perish (PoP) software. The method of searching and selecting documents based on "keywords" using the search word "job security", then all documents are selected and exported into RIS format. The Bibliometric software used to extract metadata uses VOSviewer. The results of the keyword network map visualization analysis from this study succeeded in identifying seven main clusters that represent the direction, trends, and focus of research in the field of job security. The results of this study reveal that the study of job security is not only focused on the aspect of job certainty, but develops in a multidimensional direction involving psychological, organizational, economic, and overall employee welfare factors. The contribution of this research is theoretical in nature that will enrich the knowledge base on the future direction of job security research, and practically provide recommendations to employment policymakers and HR practitioners.